Texas chainsaw [videorecording (DVD)] - Luessenhop, John; Daddario, Alexandra, 1986-; Yeager, Dan; Raymonde, Tania, 1988-; Songz, Trey; Sipos, Shaun, 1981- (Lionsgate, 2013)
In 1974, townspeople hunted down and killed every member of the Sawyer family for committing a series of grisly murders. Decades later and hundreds of miles away, a young woman learns that she has inherited a Texas estate from a grandmother she never knew she had. She finds she is the sole owner of a lavish, isolated Victorian mansion. But her newfound wealth comes at a price as she stumbles upon a horror that awaits her in the mansion's dank cellars.